FEATURES OF THE DEVELOPMENT OF INTERNATIONAL MICE TOURISM - Бакало, Надія; Маховка, Вікторія (Modern engineering and innovative technologies, 2023)
The article examines the essence and features of MICE tourism, which includes meetings - negotiations, corporate meetings; incentives – incentive tours or motivational programs for employees; conferences - conferences, forums, seminars, congresses; event